Preparation, characterisation and release of carvacrol encapsulated in gellan hydrogel and chitosan nanoparticles for antibacterial application - Hasnu, Norafida (2017)
Studies of plant materials as natural compound such as carvacrol (Carv) for antibacterial agents have gained much attention in the scientific research. It has been proven to be the potential agent in the treatment of infections and is safe for human and animal consumption. However, this free standing bioactive compound is unstable in the harsh environment conditions which easily evaporates and prone to degradation due to volatilisation and chemical reaction. In this study, the encapsulation technology helps to provide protection in order to enhance the effectiveness and the release manner thereby improving cost effectiveness of the product. Thus, Carv was encapsulated in two types of host materials which are gellan gum hydrogel thin film (GG-Carv TF) and chitosan nanoparticles (CNP-Carv). Besides that, the release properties are studied for further antibacterial application against Gram-negative bacteria, E. coli. Based on the result, GG-Carv TF showed combination of both functional groups from GG and Carv in FTIR spectra. The CHN analysis further confirmed the encapsulation as evidence of the changes in the element percentage. The swelling and degradation percentage increased with time and the decreasing patterns can be observed as the concentration of Carv increased in the range of 680.94-424.20 % and 26.83-2.67 %, respectively. Highest accumulated release of Carv from GG-Carv TF was recorded with 97.6 %. From the kinetic fitting model, pseudo-second order was observed to fit the GG-Carv TF release profile with r2 > 0.9. GG-Carv TF exhibited the significant antibacterial activity against E. coli with clear inhibition zone of 20 mm while the detection of the bacterial growth by optical density also displayed the continued decrease in sustained and controlled manner. Meanwhile, the encapsulation with the other host, CNP-Carv, the results showed the increment in the size distribution average to 139 nm prior to the blank size of CNP with only 56 nm. This result was complementary with the size of nanoparticles on surface morphology observed using FESEM. The FTIR spectrum also revealed the combination of both functional groups from the CNP and Carv, proving that Carv was successfully encapsulated. Highest accumulated release of Carv from GG-Carv TF was recorded with 28.0 %. From the kinetic fitting model, pseudo-second order was observed to fit the GG-Carv TF release profile with r2 > 0.9. CNP-Carv exhibited significant antibacterial activity against E. coli with the notable inhibition zone of 20 mm and the detection of bacterial growth by optical density also showed a continued decline of bacterial growth. Hence, the gellan gum hydrogel and chitosan nanoparticles are proven to be effective carrier of carvacrol for further antibacterial application.